THE SOLDIER - PEACE BEARER (Annual of the Faculty of Philosophy in Skopje, 2011)
Peace building and stability in the crisis regions announced new development of the relations between the peace and the soldier. The soldier being a peace bearer is more frequently happening. This paper researches new challenges that the soldier faces in the crisis regions in the period after the end of the Cold War, and makes an attempt do find an answer which most probably will form the new place and role of the soldier in the cintemporary conflict.
Keywords: PEACE; STABILITY; MILITARY ORGANIZATION; SOLDIER CONFLICT; CRISIS REGIONS; BUILDING